Understanding and Addressing Latinx COVID-19 Disparities in Washington State. (December 2020) - Baquero, Barbara; Gonzalez, Carmen; Ramirez, Magaly; Chavez Santos, Erica; Ornelas, India J.
The COVID-19 pandemic has exposed, and intensified, health inequities faced by Latinx in the United States. Washington was one of the first U.S. states to report cases of COVID-19. Public health surveillance shows that 31% of Washington cases are Latinx, despite being only 13% of the state population. Unjust policies related to immigration, labor, housing, transportation, and education have contributed to both past and existing inequities. Approximately 20% of Latinx are uninsured, leading to delays in testing and medical care for COVID-19, and early reports indicated critical shortages in professional interpreters and multilingual telehealth options. Washington State is taking action to address some of these inequities. Applying a health equity framework, we describe key factors contributing to COVID-19–related health inequities among Latinx populations, and how Washington State has aimed to address these inequities. We draw on these experiences to make recommendations for other Latinx communities experiencing COVID-19 disparities.